Case Report: Anti-N-Methyl-D-Aspartate Receptor Encephalitis in an Elderly Patient With Primary Sjögren's Syndrome - Li, Xia; Kong, Rui; Liao, Qiuju; Ye, Jing; Zhao, Yi (Frontiers in Neurology, 2021)
Neurological manifestations of primary Sjögren's syndrome (SS) are diverse involving the peripheral and central nervous system. Anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis, as the most prevalent autoimmune encephalitis, was rarely reported to be complicated with primary SS. Herein, we present an elderly patient with a 15-year history of primary SS presenting with progressive cognitive dysfunction due to anti-NMDAR encephalitis that was once misdiagnosed as primary degenerative dementia. Early recognition of anti-NMDAR encephalitis and initiation of treatment with steroids and immunosuppressant gained a favorable outcome. Our findings enhance the awareness that autoimmune encephalitis should be taken into account in the patients with primary SS presenting with progressive cognitive impairment.